2017
DOI: 10.3892/ijo.2017.4187
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG1 regulates NOB1 expression by sponging miR-326 and promotes tumorigenesis in osteosarcoma

Abstract: The long non-coding RNA (lncRNA) small nucleolar RNA host gene 1 (SNHG1) has been demonstrated to participate in the deterioration of many types of cancer. However, the underlying mechanisms of SNHG1-mediating functions in osteosarcoma (OS) have yet to be elucidated. In the present study, our results showed that SNHG1 was upregulated in OS tissues and cell lines, and high SNHG1 expression predicts poor overall survival of OS patients. Knockdown of SNHG1 inhibited cell growth and metastasis of OS in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 50 publications
7
84
1
Order By: Relevance
“…7 For example, lncRNA HOX transcript antisense RNA has been verified as an effective diagnostic marker in patients with liver, colon, breast, and pancreatic cancer. 12,13 However, the mechanism of it in PC still needs to be explored. A few studies have indicated that SNHG1 can promote the proliferation of tumor cells and decrease their apoptosis in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…7 For example, lncRNA HOX transcript antisense RNA has been verified as an effective diagnostic marker in patients with liver, colon, breast, and pancreatic cancer. 12,13 However, the mechanism of it in PC still needs to be explored. A few studies have indicated that SNHG1 can promote the proliferation of tumor cells and decrease their apoptosis in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that the basal expression of antioxidants and two-phase enzyme in Nrf2 knockout mice was markedly lower compared with wild-type mice, with sensitivity to ROS-induced cytotoxicity increased, indicating that antioxidant genes were vital to protecting against myocardial injury and the expression of Nrf2 was involved in the expression and induction of antioxidants. In addition, knockout of Nrf2 inhibited the ability of fibroblasts to fight against injury induced by ROS (33,34). Importantly, the present study demonstrated that dioscin significantly increased Nrf2 protein expression in the heart of CHD model pigs, and the results indicated that the effects of dioscin may be mediated by Sirt1/Nrf2 to protect against CHD in pigs.…”
Section: Discussionsupporting
confidence: 50%
“…However, the mechanism of SNHG1's effect on hepatocellular carcinoma has not been elucidated. Furthermore, it was demonstrated that SNHG1 acts as an important regulator of the regulation of progression of various cancers by sponging to miR-195 and miR-199a-3p [22]. Now, we investigated the influence of SNHG1 on cell migration and invasion in hepatocellular carcinoma and its relationship with miR-195.…”
Section: Introductionmentioning
confidence: 98%